Conversation as a tool of research in practical theology. Issue 5 (20th October 2019) - Jordan, Elizabeth
ABSTRACT: The study of the dynamics of conversation has been a well-established tool of research in the social sciences but, although interest in the espoused and ordinary theology of church members has grown, its use has not been well developed in Practical Theology. This article examines how attention to the manner in which conversations proceed may aid understanding of the speaker's theology, aiding both the researcher and the minister in understanding the theological assumptions of members of Christian congregations. Listening to these conversations with the aid of the discipline of Conversation Analysis has revealed theology that is extra-ordinary: insightful, relevant and missional.